The Effect of Sericin from Various Extraction Methods on Cell Viability and Collagen Production - Aramwit, Pornanong (Molecular Diversity Preservation International (MDPI), 2010)
Silk sericin (SS) can accelerate cell proliferation and attachment; however, SS can be extracted by various methods, which result in SS exhibiting different physical and biological properties. We found that SS produced from various extraction methods has different molecular weights, zeta potential, particle size and amino acid content. The MTT assay indicated that SS from all extraction methods had no toxicity to mouse fibroblast cells at concentrations up to 40 μg/mL after 24 h incubation, but SS obtained from some extraction methods can be toxic at higher concentrations. Heat-degraded SS was the least toxic to cells and activated the highest collagen production, while urea-extracted SS showed the lowest cell viability and collagen production. SS from urea extraction was severely harmful to cells at concentrations higher than 100 μg/mL. SS from all extraction methods could still promote collagen production in a concentration-dependent manner, even at high concentrations that are toxic to cells.